Kinetochore scaffold 1 regulates SAC function during mouse oocyte meiotic maturation - Yue, Wei; Wang, Yue; Meng, Tie-Gang; Zhang, Hong-Yong; Zhang, Xin-Ran; Ouyang, Ying-Chun; Hou, Yi; Schatten, Heide; Wang, Zhen-Bo; Sun, Qing-Yuan (The FASEB journal, 2022)
Precise regulation of chromosome separation through spindle assembly checkpoint (SAC) during oocyte meiosis is critical for mammalian reproduction. The kinetochore plays an important role in the regulation of SAC through sensing microtubule tension imbalance or missing microtubule connections. Here, we report that kinetochore scaffold 1 (KNL1, also known as CASC5), an outer kinetochore protein, plays a critical role in the SAC function of mouse oocytes. KNL1 localized at kinetochores from GVBD to the MII stage, and microinjection of KNL1-siRNA caused accelerated metaphase-anaphase transition and premature first meiosis completion, producing aneuploid eggs. The SAC was prematurely silenced in the presence of unstable kinetochore-microtubule attachments and misaligned chromosomes in KNL1-depleted oocytes. Additionally, KNL1 and MPS1 had a synergistic effect on the activation and maintenance of SAC. Taken together, our results suggest that KNL1, as a kinetochore platform protein, stabilizes SAC to ensure timely anaphase entry and accurate chromosome segregation during oocyte meiotic maturation.